Pengaruh Komunikasi Pemasaran Terhadap Citra Perusahaan Pada PT. Telkomsel.Tbk Kota Makassar - Sumarlin K, Andi (Universitas Negeri Makassar, 2020)
Penelitian ini bertujuan untuk mengetahui pengaruh komunikasi pemasaran terhadap citThis study aims to determine the effect of marketing communication on company image at PT. Telkomsel, Tbk. in the city of Makassar. In this study data were collected through observation and questionnaire methods on 149 respondents obtained using purposive sampling techniques and data analysis techniques used were simple regression analysis. The results of this study indicate that the marketing communication variable has a positive and significant influence on the company's image at PT. Telkomsel, Tbk. in the city of Makassar. The implication of this research is that companies must be able to maintain or even improve the quality of marketing communications to be better known by the public and be able to create a positive corporate imagera perusahaan pada PT. Telkomsel, Tbk. dikota Makassar.Dalam penelitian ini data dikumpulkan melalui metode observasi dan kuesioner terhadap 149 orang responden yang diperoleh dengan menggunakan teknik purposive sampling dan teThis study aims to determine the effect of marketing communication on company image at PT. Telkomsel, Tbk. in the city of Makassar. In this study data were colThis study aims to determine the effect of marketing communication on company image at PT. Telkomsel, Tbk. in the city of Makassar. In this study data were collected through observation and questionnaire methods on 149 respondents obtained using purposive sampling techniques and data analysis techniques used were simple regression analysis. The results of this study indicate that the marketing communication variable has a positive and significant influence on the company's image at PT. Telkomsel, Tbk. in the city of Makassar. The implication of this research is that companies must be able to maintain or even improve the quality of marketing communications to be better known by the public and be able to create a positive corporate imagelected through observation and questionnaire methods on 149 respondents obtained using purposive sampling techniques and data analysis techniques used were simple regression analysis. The results of this study indicate that the marketing communication variable has a positive and significant influence on the company's image at PT. Telkomsel, Tbk. in the city of Makassar. The implication of this research is that companies must be able to maintain or even improve the quality of marketing communications to be better known by the public and be able to create a positive corporate imageknik analisis data yang digunakan adalah analisis regresi sederhana.Hasil penelitian ini menunjukkan bahwa variabel komunikasi pemasaran mempunyai pengaruh positif dan signifikan terhadap citra perusahaan pada PT. Telkomsel, Tbk. dikota Makassar.Implikasi penelitian ini bahwa perusahaan harus mampu mempertahankan atau bahkan meningkatkan kualitas komunikasi pemasaran agar lebih dikenal oleh masyarakat dan mampu meciptakan citra perusahaan yang positif.Â